Duodenal ulceration: review of 110 cases. Issue 6 (June 1987) - Murphy, M S; Eastham, E J; Jimenez, M; Nelson, R; Jackson, R H
Abstract : This paper describes 110 cases of childhood duodenal ulcer, which were diagnosed over 26 years: 63 were diagnosed by barium meal examination; 47 by upper gastrointestinal endoscopy. The mean age at diagnosis was 11.2 years, with symptoms reported in 46% before 10 years and in 15% before 6 years of age. There was often a considerable delay in diagnosis, particularly in the younger age group. Nocturnal pain (61%) and a close family history of duodenal ulcer disease (62%) were the most valuable pointers to the diagnosis. Fifteen children had required surgery for persistent symptoms. Thirty four had received treatment with an H2 receptor antagonist, and all but four had had a satisfactory initial response. Seventy per cent relapsed within six months of discontinuing treatment, and long term maintenance treatment may therefore be necessary.